Psychometric comparison of the Persian Salzburg Emotional Eating Scale and Emotional Eater Questionnaire among Iranian adults - Sahar Ghafouri; Abbas Abdollahi; Wanich Suksatan; Supat Chupradit; Aleiia J. N. Asmundson; Lakshmi Thangavelu (Journal of Eating Disorders, 2022)
Plain English summary Emotional eating is defined as overeating in response to negative emotions. Emotional eating could lead to substantial psychological suffering as well as health issues. Therefore, measuring emotional eating is important. This study aims to examine the psychometric properties of the Salzburg Emotional Eating Scale (SEES) and the Emotional Eater Questionnaire (EEQ) among Iranian adults. Participants in the study included 489 adults who completed both questionnaires online. The results showed that the SEES and the EEQ had acceptable face and content validity; however, the SEES showed better goodness-of-fit indices and factor loading values than the EEQ. Although the SEES and the EEQ are suitable for measuring emotional eating, the SEES showed better results and the SEES is recommended for measuring emotional eating among Iranian adults.